Coated substrate and method for producing coated substrate

A coated substrate with specific composition and structure, formed using a controlled process, addresses the limitations of conventional substrates by providing high adhesion, flexibility, and functionality for diverse applications, suitable for mass production.

JP2025017994APending Publication Date: 2025-02-06NITERRA CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023121353
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

Conventional coated substrates lack sufficient functionality and versatility, and there is a need for improved substrates with high adhesion and flexibility to meet various applications.

Method used

A coated substrate with a coating thickness of 60 nm to 10 μm, containing 0.1 to 10 atm% carbon, 80 atm% total metal and oxygen elements, and a relative density of 90% or more, composed of γ-Al2O3, with a laminated structure and no oxide coating from substrate oxidation, formed using a bath liquid with low moisture and specific metal and halogen elements, and heat-treated in a non-oxidizing atmosphere.

Benefits of technology

The coated substrate exhibits high adhesion, flexibility, and functionality, suitable for various applications, enabling mass production with cost-effectiveness and high tracking ability to substrate deformation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025017994000001_ABST
    Figure 2025017994000001_ABST
Patent Text Reader

Abstract

To provide a novel coated substrate which is applicable to various fields and from which high functionality can be expected.SOLUTION: A coated substrate 1 comprises a substrate 5 coated with a film 3. The film 3 has a thickness of 60 nm or more and 10 μm or less. When the film 3 is measured, the elemental percentage of C (carbon) is 0.1 atm% or more and less than 10 atm%, and the total elemental percentage of metal elements and O (oxygen) is 80 atm% or more. The film 3 has a relative density of 90% or more, and the film 3 contains γ-Al2O3.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to coated substrates and methods of making coated substrates. [Background technology]

[0002] Patent Documents 1 to 4 disclose coated substrates with metal oxide films. In Patent Documents 1 to 4, a wet film-forming method is adopted. On the other hand, a dry film-forming method (dry process) is sometimes adopted to control the thickness according to the complex shape of the substrate. Considering the performance when applied to various fields, conventional coated substrates are not necessarily sufficient, and the development of new coated substrates has been eagerly desired. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-32521 A [Patent Document 2] JP 2009-147192 A [Patent Document 3] JP 2015-93821 A [Patent Document 4] Japanese Patent Application Publication No. 9-202606 Summary of the Invention [Problem to be solved by the invention]

[0004] The present disclosure has been made in view of the above-mentioned circumstances, and has an object to provide a novel coated substrate that can be applied to various fields and is expected to have high performance. The present disclosure can be realized in the following aspects. [Means for solving the problem]

[0005] [1] A coated substrate in which a substrate is coated with a coating, The thickness of the coating is 60 nm or more and 10 μm or less, When the coating was measured, the element percentage of C (carbon) was 0.1 atm% or more and less than 10 atm%, The total element percentage of metal elements and O (oxygen) is 80 atm% or more, The coating has a relative density of 90% or more, A coated substrate, wherein the coating comprises γ-Al2O3. [2] The coated substrate according to [1], wherein the coating has a laminated structure in cross-sectional form. [3] The coated substrate according to [1] or [2], wherein a portion of the substrate where the coating is formed has electrical conductivity. [4] The coated substrate according to [2], wherein the thickness of each layer in the laminated structure is 30 nm or more and 500 nm or less. [5] There is no oxide layer between the coating and the substrate resulting from oxidation of the substrate; or The coated substrate according to [1] or [2], wherein the thickness of the oxide film between the coating and the substrate, which is derived from oxidation of the substrate, is less than 100 nm. [6] A method for producing a coated substrate using a bath liquid containing an organic solvent, comprising the steps of: The bath liquid has a water content of less than 5% by mass, contains at least one metal element, and contains at least one halogen element; A film containing the metal element is formed on the negative electrode side of the substrate by applying a voltage to the substrate while the substrate is immersed in the bath liquid; Then, γ-Al2O3 is formed by heat treatment in a non-oxidizing atmosphere. Effect of the Invention

[0006] According to the present disclosure, a novel coated substrate is provided that is applicable to various fields and can be mass-produced. Furthermore, the coated substrate of the present disclosure has a coating that is highly adaptable to deformation of the substrate. Furthermore, the coated substrate of the present disclosure has high adhesion between the coating and the substrate. [Brief description of the drawings]

[0007] [Figure 1] FIG. 2 is a schematic diagram of a cross section of a coated substrate. [Diagram 2] FIG. [Diagram 3] FIG. 2 is a diagram showing the results of XRD measurement (X-ray diffraction peaks) in Experimental Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present disclosure will be described in detail below. In this specification, when a numerical range is described using "-", the lower limit and the upper limit are included unless otherwise specified. For example, the description "10-20" includes both the lower limit "10" and the upper limit "20". In other words, "10-20" has the same meaning as "10 or more and 20 or less". In this specification, the upper limit and the lower limit of each numerical range can be arbitrarily combined.

[0009] 1.Coated substrate 1 The coated substrate 1 is formed by coating a substrate 5 with a coating 3. The thickness of the coating 3 is 60 nm or more and 10 μm or less. When the coating 3 is measured, the element percentage of C (carbon) is 0.1 atm% or more and less than 10 atm%, and the total element percentage of metal elements and O (oxygen) is 80 atm% or more. The coating 3 has a relative density of 90% or more. The coating 3 contains γ-Al2O3.

[0010] (1) Base material 5 The substrate 5 is not particularly limited. In order to enhance the adhesion of the coating 3 to the substrate 5, at least the portion (region) of the substrate 5 covered by the coating 3 is preferably made of a material that has electrical conductivity and can become a negative electrode 7 (cathode). By making the portion of the substrate 5 covered by the coating 3 conductive and becoming a negative electrode 7 (cathode), the coating 3 can be easily formed on this portion by applying a voltage. The surface of the substrate 5 may be made of a material that is conductive and can be the negative electrode 7. The entire substrate 5 may be made of a material that can be the negative electrode 7. For example, an iron-based alloy or carbon is preferably used as the material that can be the negative electrode 7. Suitable examples of the iron-based alloy include one or more selected from Fe-Ni-Cr-based alloys (austenitic stainless steel), Fe-Cr-based alloys (ferritic stainless steel), Fe-Ni-based alloys (permalloy), Fe-Si-based alloys (iron silicon), Fe-Si-Al-based alloys (sendust), Fe-Ni-Mo (supermalloy), Fe-Co-based alloys (permendur), Fe-Ni-Co-based alloys (kovar), and Fe-CB-based alloys (amorphous).

[0011] (2) Coating 3 (2.1) Thickness The thickness of the coating 3 is 60 nm or more, preferably 200 nm or more, and more preferably 300 nm or more, from the viewpoint of exerting a function according to the material of the coating 3. On the other hand, from the viewpoint of enduring the stress generated in the coating 3 and ensuring adhesion to the substrate 5, the thickness is 10 μm or less, preferably 1000 nm or less, and more preferably 800 nm or less. From these viewpoints, the thickness of the coating 3 is 60 nm or more and 10 μm or less, preferably 200 nm or more and 1000 nm or less, and more preferably 300 nm or more and 800 nm or less. In addition, when the thickness of the coating 3 is not constant, the thickness requirement is satisfied as long as the thickness of at least a part of the coating 3 is within the above-mentioned range. The thickness of the coating 3 can be obtained by observation with a FIB-SEM (dual beam scanning electron microscope).

[0012] (2.2) Elemental percentage of C (carbon) The element percentage of C (carbon) when the coating 3 is measured by X-ray photoelectron spectroscopy (XPS method) is 0.1 atm% or more, preferably 0.5 atm% or more, and more preferably 1 atm% or more, from the viewpoint of suppressing crystal grain growth in the coating 3 and stabilizing the properties of the coating 3. On the other hand, from the viewpoint of allowing the coating 3 to fully function as an inorganic coating, it is less than 10 atm%, preferably 8 atm% or less, and more preferably 5 atm% or less. From these viewpoints, the element percentage of C (carbon) is 0.1 atm% or more and less than 10 atm%, preferably 0.5 atm% or more and 8 atm% or less, and more preferably 1 atm% or more and 5 atm% or less. Note that when the composition of the coating 3 is not constant, the requirement for the element percentage of C (carbon) is satisfied as long as the composition of at least a part of the coating 3 is within the above-mentioned range. Composition analysis by X-ray photoelectron spectroscopy can be performed using an X-ray photoelectron spectrometer. The measurement conditions are as follows: the X-ray source is aluminum metal K-alpha ray, the beam diameter is 100 μm, and the X-ray incidence angle to the surface to be analyzed is 45°, and the cross section is scanned.

[0013] (2.3) Total element percentage of metal elements and O (oxygen) The total element percentage of metal elements and O (oxygen) when the coating 3 is measured by X-ray photoelectron spectroscopy (XPS method) is 80 atm% or more, preferably 85 atm% or more, and more preferably 90 atm% or more, from the viewpoint of allowing the coating 3 to function sufficiently as an inorganic coating. The upper limit of the total element percentage of metal elements and O (oxygen) is the value obtained by subtracting the element percentage (atm%) of C (carbon) from 100 atm%. When the composition of the coating 3 is not constant, the requirement for the total element percentage of metal elements and O (oxygen) is satisfied as long as the composition of at least a part of the coating 3 is within the above-mentioned range.

[0014] (2.4) Relative density of coating 3 The relative density of the coating 3 is 90% or more, preferably 95% or more, and more preferably 98% or more, from the viewpoint of fully exerting the functions of the coating 3. The relative density of the coating 3 may be 100%. The relative density of the coating 3 is determined by the following method. A cross-sectional TEM image cut in the film thickness direction of the coating 3 is obtained. The area of ​​pores is measured in a field of view 300 nm vertically and 1000 nm horizontally. The relative density (%) is calculated using the following formula (1). The average value of the relative densities in 10 fields of view is the relative density of the coating 3. Note that if the thickness of the coating 3 is less than 300 nm vertically, the measurement is performed in a field of view that matches the thickness of the coating 3. Relative density (%) = {(S1-S2) / S1} × 100 (1) (In the formula, S1 is the area of ​​a visual field of 300 nm length × 1000 nm width (nm 2 ), and S2 is the total area of ​​the pores within a field of view of 300 nm length × 1000 nm width (nm 2 ) is)

[0015] (2.5) γ-Al2O3 The coating 3 contains γ-Al2O3. When the coating 3 contains γ-Al2O3 (γ-Al2O3 phase), the following effects are achieved. γ-Al2O3 has lower strength than α-Al2O3, but is highly flexible. When the coating contains γ-Al2O3, the coating 3 is more able to conform to the substrate 5 when the substrate 5 is deformed due to mechanical or thermal expansion.

[0016] (2.6) Laminated structure It is preferable that the coating 3 has a layered structure in cross section. The layered structure of the coating 3 can be confirmed by observing a cross section of the coating 3 cut in the thickness direction with a FIB-SEM (dual beam scanning electron microscope). When the coating 3 has a layered structure, internal cracks in the coating 3 and peeling between the coating 3 and the substrate 5 can be suppressed.

[0017] (2.7) Thickness of each layer in the laminated structure The thickness of each layer in the laminated structure is not particularly limited. The thickness of each layer is preferably 30 nm or more and 500 nm or less, more preferably 60 nm or more and 200 nm or less, and even more preferably 80 nm or more and 150 nm or less, from the viewpoint of ensuring the strength of the coating 3. The thickness of each layer can be determined by observing a cross section of the coating 3 cut in the thickness direction with a FIB-SEM (dual beam scanning electron microscope).

[0018] (2.8) Oxide film It is preferable that there is no oxide film between the coating 3 and the substrate 5 resulting from oxidation of the substrate 5, or that the thickness of the oxide film between the coating 3 and the substrate 5 resulting from oxidation of the substrate 5 is less than 100 nm. When this requirement is satisfied, the adhesion of the coating 3 to the substrate 5 is improved, and the coating 3 is more likely to conform to the substrate 5 when the substrate 5 is deformed due to mechanical or thermal expansion. The presence or absence and thickness of an oxide film can be determined by observing a cross section of the coating 3 cut in the thickness direction with a FIB-SEM (dual beam scanning electron microscope).

[0019] (2.9) Halogen elements When the coating 3 is measured by X-ray photoelectron spectroscopy, the percentage of the halogen element is preferably 0.1 atm% or more, more preferably 0.3 atm% or more, and even more preferably 0.5 atm% or more. The upper limit of the percentage of the halogen element is 3 atm% or less. It is believed that the inclusion of a trace amount of halogen element in the coating 3 removes the oxide film present on the surface of the substrate 5 by the action of the halogen element, resulting in a structure in which the coating 3 and the substrate 5 are in direct contact with each other, thereby ensuring adhesion between the substrate 5 and the coating 3. From the viewpoint of rapidly progressing the organic electrochemical reaction and allowing the coating 3 to function as a good protective film for the substrate 5, the halogen element is preferably at least one selected from the group consisting of I (iodine), Cl (chlorine), and Br (bromine).

[0020] (2.10) Metal elements The metal element is not particularly limited. From the viewpoint of easily forming a coating 3 having improved strength by a manufacturing method described later, the metal element is preferably at least one selected from the group consisting of Al (aluminum), Ti (titanium), Zr (zirconium), Mo (molybdenum), W (tungsten), V (vanadium), Fe (iron), Cr (chromium), Co (cobalt), and Mn (manganese).

[0021] 2. Method for producing coated substrate 1 The method for producing the coated substrate 1 of the present disclosure is not particularly limited. A preferred manufacturing method will be described below. The preferred manufacturing method is a method for manufacturing the coated substrate 1 using a bath liquid 2 using an organic solvent as a solvent. The bath liquid 2 has a moisture content of less than 5 mass %, contains at least one metal element, and contains at least one halogen element. This manufacturing method has a forming step of forming a coating 3 containing a metal element on the substrate 5 on the negative electrode 7 side (cathode side) by applying a voltage while the substrate 5 is immersed in the bath liquid. In addition, this manufacturing method also forms γ-Al2O3 by heat treatment in a non-oxidizing atmosphere after the forming step (heat treatment step). In the manufacturing method of the present disclosure, by electrodeposition on the negative electrode 7 side, oxidation of the substrate 5 can be suppressed more effectively than by electrodeposition on the positive electrode 6 side (anode side).

[0022] (1) Bath liquid 2 The bath liquid 2 contains an organic solvent as a solvent. (1.1) Moisture content From the viewpoint of ensuring the homogeneity of the coating 3 and suppressing oxidation of the substrate 5, the water content of the bath liquid 2 is set to less than 5 mass%. The water content is preferably less than 3 mass%, and more preferably less than 0.1 mass%. The water content may be 0 mass%. The water content of the bath liquid 2 can be determined by GC-MS analysis.

[0023] (1.2) Metal elements The bath liquid 2 contains at least one metal element. The metal element is not particularly limited. From the viewpoint of making the coating 3 function as a good protective film for the substrate 5, the metal element is preferably at least one selected from the group consisting of Al (aluminum), Ti (titanium), Zr (zirconium), Mo (molybdenum), W (tungsten), V (vanadium), Fe (iron), Cr (chromium), Co (cobalt) and Mn (manganese). In the manufacturing method of the present disclosure, an oxide film, which is the coating 3, is formed depending on the metal element in the bath liquid 2. The metal element contained in the bath liquid 2 may be supplied to the bath liquid 2 by dissolution from the positive electrode 6 (anode). When the metal element dissolves from the positive electrode 6 into the bath liquid 2, it becomes easy to control the film formation rate, and it becomes possible to continuously and stably form films on a plurality of substrates 5. When the metal element is supplied to the bath liquid 2 by dissolution from the positive electrode 6, it is preferable that the positive electrode 6 be at least one type of electrode selected from an Al electrode, a Ti electrode, and a Mo electrode. The metal elements in the bath liquid 2 may be supplied from metal alkoxides and / or inorganic metal compounds. When the metal elements are supplied by dissolving metal alkoxides and / or inorganic metal compounds, it is possible to deal with elements that are difficult to supply by dissolving the positive electrode 6 (anode). In this case, it is also possible to form a film in which a composition ratio is controlled by combining a plurality of metal elements. Examples of metal alkoxides include aluminum alkoxides, titanium alkoxides, and molybdenum alkoxides. Examples of aluminum alkoxides include aluminum trialkoxides. Examples of aluminum trialkoxides include aluminum tripropoxides (e.g., aluminum triisopropoxide, aluminum tri-n-propoxide), aluminum triethoxide, aluminum tributoxides (e.g., aluminum trisec-butoxide, aluminum tri-n-butoxide), and the like. Examples of titanium alkoxides include titanium trialkoxides and titanium tetraalkoxides, and preferably titanium tetraalkoxides. Examples of titanium tetraalkoxides include titanium tetrapropoxides (e.g., titanium tetraisopropoxide, titanium tetra n-propoxide, etc.), titanium tetramethoxide, titanium tetraethoxide, titanium tetrabutoxides (e.g., titanium tetraisobutoxide, titanium tetra n-butoxide, etc.), titanium tetrapentoxide, titanium tetrahexoxide, titanium tetra(2-ethylhexoxide), etc. Examples of the inorganic metal compound include aluminum chloride, aluminum bromide, aluminum iodide, and titanium iodide. When the metal element in the bath liquid 2 is supplied from a metal alkoxide and / or an inorganic metal compound, the concentration of the metal element in the bath liquid 2 is not particularly limited. In this case, from the viewpoint of forming a good coating 3, the concentration of the metal element in the bath liquid 2 is preferably 1 ppm or more and 100 ppm or less, more preferably 3 ppm or more and 10 ppm or less, and even more preferably 4 ppm or more and 6 ppm or less. Here, "ppm" stands for "parts per million" and "mg / L". In addition, when the bath liquid 2 contains multiple metal elements, the concentration of the metal element means the total concentration of the multiple metal elements. The concentration of the metal element in the bath liquid 2 can be measured by ICP-MS analysis.

[0024] (1.3) Halogen elements The bath liquid 2 contains at least one type of halogen element. By containing a halogen element in the bath liquid 2, the film formation is carried out at a practical speed, and the film 3 is likely to be homogeneous. The halogen element is not particularly limited. From the viewpoint of rapidly progressing the organic electrochemical reaction and allowing the film 3 to function as a good protective film for the substrate 5, the halogen element is preferably at least one selected from the group consisting of Cl (chlorine), Br (bromine), and I (iodine). The concentration of the halogen element in the bath liquid 2 is not particularly limited. From the viewpoint of appropriately suppressing the reaction rate, being advantageous in controlling the uniformity and thickness of the coating 3, and suppressing peeling of the coating 3, the concentration of the halogen element is preferably 1 ppm or more and 20,000 ppm or less, more preferably 5 ppm or more and 2,000 ppm or less, and even more preferably 10 ppm or more and 100 ppm or less. Note that "ppm" means "parts per million" and "mg / L". The concentration of the halogen element in the bath liquid 2 can be determined from the amount of halogen element added when the bath is made, or by ICP-MS analysis of the bath liquid.

[0025] (1.4) Organic solvents By using an organic solvent as the solvent for the bath liquid 2, gas generation during film formation and oxidation of the substrate 5 itself are suppressed. From the viewpoint of favorable formation of the film 3, it is preferable that the solvent contains at least one selected from the group consisting of ketones and nitriles. It is presumed that the inclusion of a ketone or nitrile in the solvent causes a condensation reaction to occur on the electrode surface (cathode surface), making electrodeposition possible. It is also presumed that the inclusion of a ketone in the solvent causes keto-enol tautomerism in the presence of a halogen, improving the reactivity of the bath liquid 2.

[0026] (1.4.1) Ketones The ketone is not particularly limited as long as it is an organic solvent having a carbonyl group (-C(=O)-) other than an ester bond. Examples of ketones include acetone, methyl ethyl ketone (MEK), 1-hexanone, 2-hexanone, 4-heptanone, 2-heptanone (methyl amyl ketone), 1-octanone, 2-octanone, 1-nonanone, 2-nonanone, diisobutyl ketone, methyl isobutyl ketone, acetylacetone, acetonylacetone, phenylacetone, acetophenone, methyl naphthyl ketone, cyclohexanone (CHN), methylcyclohexanone, etc. Among these, from the viewpoint of particularly favorable formation of the coating 3, acetone and methyl ethyl ketone are preferred as the ketone.

[0027] (1.4.2) Nitriles The nitrile is an organic solvent containing a nitrile group (-CN) in the structure. Examples of the nitrile include acetonitrile, propionitrile, valeronitrile, butyronitrile, etc. Among these, acetonitrile is preferable as the nitrile from the viewpoint of forming the coating 3 particularly well.

[0028] (2) Base material 5 For the "substrate 5", the explanation in the "(1) Substrate 5" section in "1. Coated substrate 1" above applies as is.

[0029] (3) Forming step of forming the film 3 (voltage application) In the present disclosure, a voltage is applied while the substrate 5 is immersed in the bath liquid to form a coating 3 on the negative electrode side of the substrate 5. Specifically, a positive electrode 6 and a negative electrode 7 (substrate 5) are immersed in the bath liquid 2 to generate a potential gradient between the two electrodes. Any known conductive substrate can be used as the positive electrode 6. When the metal element in the bath liquid 2 is supplied by dissolution from the positive electrode 6, the positive electrode 6 is preferably at least one electrode selected from an Al electrode, a Ti electrode, and a Mo electrode. The shape, thickness, size, etc. of the positive electrode 6 are not particularly limited. The positive electrode 6 may be, for example, in the form of a foil, a plate, a foam, a nonwoven fabric, a mesh, a felt, or an expanded form. The positive electrode 6 and the negative electrode 7 are preferably disposed opposite each other. The positive electrode 6 and the negative electrode 7 are connected to a DC power supply, and a potential gradient can be generated between the positive electrode 6 and the negative electrode by the DC power supply. In order to generate a potential gradient between the positive electrode 6 and the negative electrode 7, the positive electrode 6 and the negative electrode 7 are immersed in the bath liquid 2 and a voltage (e.g., a constant voltage) is applied to both electrodes by a power source connected to the positive electrode 6 and the negative electrode 7. From the viewpoint of forming a film at a practical speed, the potential gradient generated between the two electrodes is preferably 10 V or more and 300 V or less, more preferably 20 V or more and 100 V or less, and even more preferably 60 V or more and 80 V or less, in the case of a constant voltage. The application time of the voltage is not particularly limited, and is, for example, preferably from 10 seconds to 300 seconds, more preferably from 30 seconds to 240 seconds, and even more preferably from 60 seconds to 180 seconds. The voltage does not have to be a constant voltage, and may be variable in magnitude. The forming step may be performed once or multiple times. By repeating the forming step multiple times, it is possible to thicken the coating 3. By repeating the forming step multiple times in this manner, it is possible to construct a layered structure of the coating 3 (layered horizontal stripe structure).

[0030] (4) Heat treatment process By heat treatment in a non-oxidizing atmosphere, γ-Al2O3 can be selectively produced in the coating 3. The non-oxidizing atmosphere may be a reducing atmosphere, an inert atmosphere, or a vacuum atmosphere. The oxygen concentration in the non-oxidizing atmosphere is preferably less than 100 ppm. The heat treatment temperature is not particularly limited. From the viewpoint of selectively producing γ-Al2O3, the heat treatment temperature is preferably 800° C. or more and 1300° C. or less, more preferably 900° C. or more and 1200° C. or less, and even more preferably 950° C. or more and 1050° C. or less. The heat treatment time is not particularly limited. From the viewpoint of selectively producing γ-Al2O3, the heat treatment time is preferably from 0.25 hours to 3 hours, more preferably from 0.5 hours to 2 hours, and even more preferably from 0.75 hours to 1 hour.

[0031] (5) Relationship between the formation process and the heat treatment process When the step of forming the coating 3 is carried out a plurality of times, a heat treatment step may be carried out after the final forming step. Furthermore, when the forming step of forming the coating 3 is performed multiple times, a heat treatment step may be performed between the forming steps. In this case, a heat treatment step may be performed between all of the forming steps. Furthermore, there may be a mixture of cases where a heat treatment step is performed and cases where it is not performed between the forming steps. Note that, even when the forming step of forming the coating 3 is performed multiple times and a heat treatment step is performed between the forming steps, the heat treatment step may be performed after the final forming step.

[0032] 3. Effects of this embodiment According to the present embodiment, a novel coated substrate 1 is provided that is applicable to various fields and is expected to provide high functionality. According to this embodiment, it is possible to form the coating 3 that has excellent adhesion to the substrate 5. In addition, the coating 3 can be made thicker than before. In the coated substrate 1 of this embodiment, a protective film of a dense γ-Al2O3 crystal phase is formed, and therefore the coating 3 has high conformability to the substrate 5 when the substrate 5 is deformed due to mechanical or thermal expansion. The coated substrate 1 of this embodiment can be mass-produced by employing a simple process. The coated substrate 1 of the present embodiment is advantageous in terms of cost because it can be formed without using expensive raw materials or using only small amounts of expensive raw materials. The film formation mechanism in this embodiment is assumed to be as follows. It is assumed that a condensation reaction occurs at the cathode while incorporating metal elements in the solvent, followed by an oxide film formation process in which condensation and hydrolysis occur on the surface of the substrate 5 due to the heat of vaporization during drying. However, this film formation mechanism is merely assumed, and the present disclosure is not bound by this film formation mechanism. EXAMPLES

[0033] The present disclosure will be explained more specifically with reference to examples. In the following description, the measurement conditions for XPS (X-ray photoelectron spectroscopy) are as follows. [Measurement conditions] X-ray beam diameter: 100μmΦ Signal capture angle: 45.0° Pass energy: 140 eV Measured after Ar etching for 30 seconds (etching rate: 10 nm / min in SiO2 equivalent)

[0034] 1. Experimental example (solvent: acetone, positive electrode 6: aluminum) (1) Preparation of coated substrate 1 A film forming apparatus 11 shown in FIG. 3 was used. An aluminum wire was used as the positive electrode 6. A Kovar plate was used as the negative electrode 7. The negative electrode 7 was a substrate 5 on whose surface a coating 3 was formed. Acetone was used as the solvent for the bath liquid 2. 50 ppm of iodine was dissolved in the bath liquid 2 as a halogen. The formation step of applying 80 V between the positive electrode 6 and the negative electrode 7 for 1 minute while the positive electrode 6 and the negative electrode 7 were immersed in the bath liquid 2 was repeated 9 times. Thereafter, heat treatment was performed in a non-oxidizing atmosphere (a reducing atmosphere using hydrogen gas) at 1000° C. for 45 minutes.

[0035] (2)Various measurement results When the cross section of the negative electrode 7 was observed by FIB-SEM (field emission scanning electron microscope), it was found that the coating 3 having a multilayer structure and a total thickness of 600 nm was formed on the surface of the substrate 5. The thickness of each layer was 50 nm or more and 100 nm or less. It was also confirmed by this observation that no oxide coating resulting from oxidation of the substrate 5 was present between the coating 3 and the substrate 5. Analysis by XPS after 30 seconds of Ar etching revealed that this film 3 was aluminum oxide. Furthermore, the element percentage of carbon element in the coating 3 was 5.8 atm %, and the total element percentage of aluminum element and oxygen element was 93.9 atm %. The element percentage of iodine in this film 3 was 0.1 atm %. Furthermore, when Coating 3 was analyzed by XRD (X-ray diffraction) before and after heat treatment, black dot peaks derived from γ-Al2O3 that were not present before heat treatment were observed after heat treatment, as shown in Figure 3. This result demonstrated that γ-Al2O3 was produced in Coating 3 by the heat treatment. Furthermore, the relative density of the coating 3 was determined by the following method and was found to be 100%. The relative density of the coating 3 was determined by the following method. A cross-sectional TEM image was obtained cutting the coating 3 in the film thickness direction. The area of ​​pores was measured in a visual field of 300 nm vertically and 1000 nm horizontally. The relative density (%) was calculated using the following formula (1). The average value of the relative densities in 10 visual fields is the relative density of the coating 3. Note that when the thickness of the coating 3 is less than 300 nm vertically, the measurement is performed in a visual field that matches the thickness of the coating 3. Relative density (%) = {(S1-S2) / S1} × 100 (1) (In the formula, S1 is the area of ​​a visual field of 300 nm length × 1000 nm width (nm 2 ), and S2 is the total area of ​​the pores within a field of view of 300 nm length × 1000 nm width (nm 2 ) is)

[0036] 2. Effects of the embodiment According to this embodiment, a novel coated substrate 1 is provided which is applicable to various fields and is expected to provide high functionality.

[0037] The present invention is not limited to the above-described embodiments, and various modifications and variations are possible within the scope of the claims of the present invention.

[0038] (Additional Note) This specification includes the following inventions: [1] A coated substrate in which a substrate is coated with a coating, The thickness of the coating is 60 nm or more and 10 μm or less, When the coating was measured, the element percentage of C (carbon) was 0.1 atm% or more and less than 10 atm%, The total element percentage of metal elements and O (oxygen) is 80 atm% or more, The coating has a relative density of 90% or more, A coated substrate, wherein the coating comprises γ-Al2O3. [2] The coated substrate according to [1], wherein the coating has a laminated structure in cross-sectional form. [3] The coated substrate according to [1] or [2], wherein a portion of the substrate where the coating is formed has electrical conductivity. [4] The coated substrate according to [2] or [3], wherein the thickness of each layer in the laminated structure is 30 nm or more and 500 nm or less. [5] There is no oxide layer between the coating and the substrate resulting from oxidation of the substrate; or The coated substrate according to any one of [1] to [4], wherein the thickness of the oxide film between the coating and the substrate, which is derived from oxidation of the substrate, is less than 100 nm. [6] A method for producing a coated substrate using a bath liquid containing an organic solvent, comprising the steps of: The bath liquid has a water content of less than 5 mass %, contains at least one metal element, and contains at least one halogen element; A film containing the metal element is formed on the negative electrode side of the substrate by applying a voltage while the substrate is immersed in the bath liquid; Then, γ-Al2O3 is formed by heat treatment in a non-oxidizing atmosphere. [Explanation of symbols]

[0039] 1 ...Coated substrate 2…Bath liquid 3. Coating 5...Base material 6...Positive electrode 7...Negative electrode 11...Film deposition equipment

Claims

1. A coated substrate in which a substrate is coated with a coating, The thickness of the coating is 60 nm or more and 10 μm or less, When the coating was measured, the element percentage of C (carbon) was 0.1 atm % or more and less than 10 atm %, The total element percentage of metal elements and O (oxygen) is 80 atm % or more, The coating has a relative density of 90% or more, The coating is made of γ-Al 2 O 3 A coated substrate comprising:

2. The coated substrate according to claim 1 , wherein the coating has a laminated structure in cross-sectional form.

3. The coated substrate according to claim 1 or 2, wherein a portion of the substrate where the coating is formed has electrical conductivity.

4. The coated substrate according to claim 2 , wherein the thickness of each layer in the laminate structure is 30 nm or more and 500 nm or less.

5. There is no oxide layer between the coating and the substrate resulting from oxidation of the substrate; or 3. The coated substrate according to claim 1 or 2, wherein the thickness of the oxide film between the coating and the substrate resulting from oxidation of the substrate is less than 100 nm.

6. A method for producing a coated substrate using a bath liquid containing an organic solvent, comprising the steps of: The bath liquid has a water content of less than 5 mass %, contains at least one metal element, and contains at least one halogen element; A film containing the metal element is formed on the negative electrode side of the substrate by applying a voltage to the substrate while the substrate is immersed in the bath liquid; Then, heat treatment in a non-oxidizing atmosphere turns the γ-Al 2 O 3 The method of manufacturing a coated substrate comprising forming

Citation Information

Patent Citations

  • Multilayer oxide thin film element and its production

    JP1997202606A

  • Crystalline inorganic film and method of manufacturing the same, and semiconductor device

    JP2009147192A

  • CSD solution, and CIS-based film forming method using the solution

    JP2011032521A

  • Method of producing titanium oxide film, and titanium oxide film

    JP2015093821A